PEMBELAJARAN SENI TARI DI SMP NEGERI 1 BATANGAN KABUPATEN PATI - Dyah Ayu K, Rakanita; Malarsih, Malarsih (Jurnal Seni Tari, 2013)
This study aims to identify and describe the process of learning the art of dance in the subjects of art and culture in SMP N egeri 1   Pati Bars Bars district. This study used a qualitative approach, the target location  peneletian in SMP  Negeri 1 Pati Bars district.  Data  analysis  techniques  by  reducing,  presenting  data  and  infer  all  the  information  correctly.  The  results  in the learning  process  SMPN1  dance  bars  in  the  teaching  and  learning   activities   to  implement  the  learning  stages such   as preparation,   delivery,   training,   and   performance.   Dance   teachers  implementing  these   stages  in   order   to improve  student learning outcomes and the effectiveness of the time. The factors that affect the learning process of dance is a factor  suppor ting and inhibiting factors.  From the results of the research described the conclusion can be drawn in the learning process SMPN1 Bars activities include the activities of the learning process, preliminary, activities, core and cover. In addition, teacher s also use audio-visual media like Laptop, LCD, Projectors and VCD Cassette Dance. Suggestions relating to the process of learning the art of dance culture in SMP eri 1 District Bars Bars are For teachers in the use of audio -visual media enhanced user creativity, so  that   students  do  not  feel  bored  at  dance   lessons.  Infrastructure  needs  plus  room   art   glass  wall,  in  order  to facilitate  the students in the dance practice. Students are expected to have their own dance VCD, so can be used for self -study.